The Development of Android-Based PowerPoint Learning Media on Wave Material to Determine the Learning Interests of Class XI High School Students - Sukroyanti, Baiq Azmi; Herayanti, Lovy; Bakti, Agus Mulia (Department of Physics Education, Universitas Mataram, 2024)
Technological advancements in education have enabled the development of more interactive and easily accessible learning media for students. One such innovation is the use of an Android-based PowerPoint application, which can be utilized both offline and online to enhance students' interest and engagement in learning. This study aims to evaluate the feasibility of using an Android-based PowerPoint application, measure the responses of students at SMAN 1 Lenek to the application, and assess the differences in students' learning interest before and after using this learning media. The research employs a Research and Development (R&D) methodology, following six procedural stages: problem potential analysis, observation and assessment, design and development, product testing, revision, and implementation. Data were analyzed using the ideal standard deviation method and normalized gain. The ideal standard deviation method was employed to assess the validity of the instruments evaluated by media and material experts, as well as to measure the students' responses to the application. Normalized gain was used to determine the change in learning interest scores from questionnaires distributed before and after the learning process. The results of the study indicate that the developed Android-based PowerPoint application successfully increased the learning interest of 11th-grade science students at SMAN 1 Lenek, with a gain score of 0.225, categorized as low. The students' responses to the use of this application were very positive, with an overall average score of 4.4. This research successfully developed an Android-based PowerPoint application that can be accessed both offline and online, contributing positively to the improvement of learning quality.